PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill) PADA BERBAGAI MEDIA TUMBUH DENGAN INTERVAL PENYIRAMAN AIR KELAPA YANG BERBEDA - Totong, Oskar; Hadid, Abdul; Mas’ud, Hidayati (AGROTEKBIS, 2016)
This research was carried out at the Green House Experimental Farm Science Park, Sigi Biromaru Sidondo sub-district, Sigi Regency, since April - July 2016. This research aims to determine the effect of different types of media is growing and the interval giving coconut water towards growth and yield of tomato plants with uses a Completely Randomized Design (CRD) two factors, where the first factor is the growing medium consisting of four levels treatments, M1 (medium soil and chicken manure), M2 (ground husk charcoal and media), M3 (medium soil and sawdust), M4 (medium soil and cow manure), and the second factor is the interval watering coconut water is P1 (4 days), P2 (8 days), and P3 (12 days). Each combination treatment was repeated three times so that there are 36 experimental units. The data were analyzed using analysis of variance, and the real effect then tested further using Honestly Significant Difference at 5% level. The results showed that the treatment M2P2 give very good influence on the growth phase of height with an average 121,67 cm at age 45 days after planting, the average number of leaves 268,67 strands, and the total dry weight of the average plant 204,67 g, whereas treatment M1P1 give very good influence on the amount of fruit on average of 7,67 with a total weight of ripe fruit average 243, 67 g and the average root volume 19,67 ml.Key Words : Tomato, Growing Media, Coconut Water.